Internal impingement: Long-term results of capsular shoulder shrinking and up-to-date treatment anno 2007 - Jansen, N.; Declerq, G. (Medicine and Science in Tennis, 2007)
Authors evaluated the long-term results of arthroscopic electrothermal shrinkage of internal impingement in competition athletes. In the study they only included high level, overhead athletes with a history of longstanding pain in their dominant shoulder due to internal impingement. In this series, ten men and two woman were included. All patients were high level overhead athletes who performed in different sports (volleyball, baseball, tennis and swimming).